MATERIAL DEPOSITION PROCESSES THROUGH ELECTRIC DISCHARGES - A REVIEW - Ana Cristina Iuga; Liviu Daniel Ghiculescu (Nonconventional Technologies Review)
The application of hard coatings is widely used in industry as a method of preventing mechanical parts from corrosion, temperature extremes, stress, and other hostile environments. An innovative method of surface modification, electrical discharge deposition (EDD) involves coating a layer of material on a part to improve its surface properties or develop new functions. Electrical Discharge Deposition (EDD) is a hybrid coating technique that has the advantage of being less expensive than other similar techniques. The technology is different from electrical discharge machining (EDM), this process deposits metal by exploiting the electrode's high wear rate. It provided a comprehensive review of the EDD process for a variety of materials, as well as details of the types and main parameters of the process, as well as a description of the characteristics of the coatings obtained.